Explaining differences in perceived health-related quality of life: a study within the Spanish population - Jesús Martín-Fernández; Gloria Ariza-Cardiel; Elena Polentinos-Castro; Teresa Sanz-Cuesta; Antonio Sarria-Santamera; Isabel del Cura-González (Elsevier, 2018)
Objective: To assess the burden of several determinants on health-related quality of life (HRQOL) and to study its heterogeneity among the different Spanish regions. Method: Cross-sectional study. Data were obtained from the Spanish National Health Survey (2012), and HRQOL was measured using the EQ-5D-5L questionnaire (utility and visual analogue scale -VAS- scores). Demographic variables, physical health condition, social variables, mental health status, and lifestyle were also analysed. Tobit regression models were employed to study the relationships between expressed HRQOL and personal characteristics. Results: A total of 20,979 surveys were obtained. Of them, 62.4% expressed a utility score of 1, corresponding to perfect health (95%CI: 61.8%-63.2%), and 54.2% showed VAS scores ≥80 (95%CI: 53.5%-54.9%). HRQOL was mainly described as a function of age, chronic limitation in daily activities, and mental health status. Belonging to a higher-class strata and physical activity were related to better self-perceived HRQOL. Ageing worsened perceived HRQOL, but did not influence its determinants, and differences in HRQOL by regions were also not significant after model adjustment. Conclusion: HRQOL perception in the Spanish population varied slightly depending on the measure used (utilities index or VAS). Age, chronic limitations in daily life, and mental health status best explained the variability in perception, and no meaningful differences in HRQOL perception among regions were found after adjustment. Resumen: Objetivo: Evaluar la carga de ciertos determinantes de la calidad de vida relacionada con la salud (CVRS) y su heterogeneidad entre diferentes regiones españolas. Métodos: Estudio transversal. Utilizando datos de la Encuesta Nacional de Salud (2012), se midió la CVRS con el cuestionario EQ5D-5L (utilidad y escala visual analógica [EVA]). Se analizaron variables demográficas, estado de salud, variables sociales, salud mental y estilos de vida, utilizando modelos Tobit. Resultados: Se incluyeron 20.979 encuestas. El 62,4% de los sujetos expresó una utilidad de 1, perfecta salud (intervalo de confianza del 95% [IC95%]: 61,8% -63,2%), y el 54,2% mostró puntuaciones en la EVA ≥80 (IC95%: 53,5%-54,9%). La CVRS se vio modificada fundamentalmente por la edad, la limitación crónica en las actividades diarias y el estado de salud mental. La clase social alta y la actividad física aparecían relacionadas con una mejor CVRS. La edad empeoró la percepción de la CVRS, pero no se asoció con un cambio en la influencia de sus determinantes. Después de ajustar los modelos, no había diferencias en la CVRS en las diferentes regiones. Conclusión: La percepción de la CVRS en la población española varió dependiendo de la medida utilizada (utilidades o EVA). La edad, las limitaciones crónicas en la vida diaria y el estado de salud mental explicaban fundamentalmente las diferencias en la CVRS, y las diferencias entre regiones se explicaron principalmente por diferentes características poblacionales. Keywords: Quality of life, Health status, Population characteristics, Public health, Palabras clave: Calidad de vida, Estado de salud, Características poblacionales, Salud pública